Chapter Life Cycle Inventory (LCI) Modeling of Municipal Solid Waste (MSW) Management Systems in Kosodrza, Community of Ostrów, Poland: A Case Study - Bieda, Bogusław (InTechOpen, 2019)
The purpose of this study is to perform the life cycle assessment (LCA) limited to life cycle inventory (LCI) related to municipal solid waste operating in Kosodrza, community of Ostrów, in Poland. The current LCI is a representative for year 2015 by application of PN-EN ISO 14040. The system boundary was labeled as gate-to-gate. The data used in this study, involving consumption of energy and fuels, water, materials, and waste, is obtained from (i) site-specific measured or calculated data and (ii) secondary data taken from integrated permit issued by Marshal of the Podkarpackie region in Rzeszów for the establishment of municipal services in Ostrów by entering the records concerning the waste landfill in Kosodrza. This study is based on the deterministic approach to LCI. Hence, uncertainty analysis is not carried out. The LCI model can be used in full LCA study.